Korelasi Nilai Bed Occupancy Rate dengan Jumlah Kunjungan Pasien di RSUD Lubuk Basung - Melati Anala; Yastori Yastori; Syamsul Kamal (AKADEMI PEREKAM DAN INFORMASI KESEHATAN (APIKES) IRIS PADANG, 2021)
Bed Occupancy Rate (BOR) data can be used to determine the level of service, to know the quality of hospital.The purpose of this paper is to determine the correlation or drill value with number patient visits at Lubuk Basung Hospital for the January-Februay 2017 periode.The data processed is secondary data of inpatients at Lubuk Basung Hospital for the January-February 2017 period, data obtained for 300 patients with a total of 109 beds, then data processing is carried out using the Microsoft Exel application program and utilizing the Pivot Table feature.Statistical processing was analyzed and presented in the form of tables and graphs by Barber Johnson.The results of data processing obtained a BOR of 28.80%, not efficient because the BOR is 60-85% efficient.BTR is 33 times, not efficient because BTR is 40-50 times a year.TI is 8 days, inefficient because it is 1-3 days efficient and ALOS is 4 days, inefficient because it is 6-9 days efficient. Based on the RL4a report,the highest age group was the 45-64 year age group with 78 patients, the highest gender grouping was male 153 patients and female 147 patients.Based on the living disposition of 295 patients, 5 patients died.The distribution of patients by region was mostly in Agam with 259 patients. The highest diagnosis was Pneumonia, Unspecified with a code of J18.9 with 27 diagnoses.The main diagnosis grouping based on defecation in ICD-10, the highest diagnosis was Chapter I, namely Certain Infectious and Parasite Disease with 20.67% totaling 62 diagnoses. There is a positive correlation between the number of patient visits and the number of bed usage.